2003
DOI: 10.1038/nm820
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal regulation of inflammation and lipid metabolism by liver X receptors

Abstract: Macrophages have important roles in both lipid metabolism and inflammation and are central to the pathogenesis of atherosclerosis. The liver X receptors (LXRs) are established mediators of lipid-inducible gene expression, but their role in inflammation and immunity is unknown. We demonstrate here that LXRs and their ligands are negative regulators of macrophage inflammatory gene expression. Transcriptional profiling of lipopolysaccharide (LPS)-induced macrophages reveals reciprocal LXR-dependent regulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

47
1,042
2
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,098 publications
(1,097 citation statements)
references
References 40 publications
47
1,042
2
6
Order By: Relevance
“…Accumulation of cholesterol crystals in the cytoplasm of macrophages was also proposed to stimulate a proinflammatory cascade 37. Alternatively, lipoprotein‐derived oxysterols are natural liver X receptor ligands, which can counter‐regulate induction of inflammatory gene expression by NF‐κB by recruiting corepressors to the promoters of inflammatory genes 37, 38, 39. Thus, we asked whether increases in plasma cholesterol that significantly accelerate atherosclerosis development would actually affect the inflammatory balance of lesional foam cells.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of cholesterol crystals in the cytoplasm of macrophages was also proposed to stimulate a proinflammatory cascade 37. Alternatively, lipoprotein‐derived oxysterols are natural liver X receptor ligands, which can counter‐regulate induction of inflammatory gene expression by NF‐κB by recruiting corepressors to the promoters of inflammatory genes 37, 38, 39. Thus, we asked whether increases in plasma cholesterol that significantly accelerate atherosclerosis development would actually affect the inflammatory balance of lesional foam cells.…”
Section: Discussionmentioning
confidence: 99%
“…Modified PS and stanols have been shown to modify the cholesterol influx and efflux from cells by altering nuclear hormone receptor activity, although it is still under discussion whether such a direct effect on the gene level can be considered one of the key mechanisms of action of PS (Plat and Mensink, 2002;Kaneko et al, 2003;Plosch et al, 2004;Calpe-Berdiel et al, 2005). The potential effect on nuclear hormone receptors could also influence gene expression of inflammatory mediators such as iNOS, COX-2 and IL-6 (Joseph et al, 2003). PS or stanols could thus directly have an impact on inflammation and plasma markers of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In mice model, it has been reported that inflammation can insult many different metabolic pathways, ultimately affect the growth of animals (Joseph et al, 2003). Skeletal muscle as a major mass peripheral tissue accounts for 40% of total BW, and is the main product of animals for slaughter.…”
Section: Introductionmentioning
confidence: 99%